Hope in the Anthropocene : agency, governance and negation / edited by Valerie Waldow, Pol Bargués and David Chandler. - Waldow, Valerie; Bargués-Pedreny, Pol; Chandler, David, 1962- (Edinburgh University Press, 2024)
Through incorporating contemporary approaches to both theory and policy practice, including critical, feminist, black and indigenous perspectives, this book analyses how Hope works with the uncertainties and interdependencies of human agency and interaction. It draws out the problems of integrating Hope into governance and policy management, and engages with Hope as a potentially negating force, in a world which can be seen as one of unending catastrophe.